(untitled) (Journal of Artificial Intelligence Research, 2023)
The life insurance industry relies heavily on accurate mortality risk prediction to ensure financial stability and offer competitive products. Traditional underwriting methods, primarily dependent on self-reported data and medical history, often lack the granularity to capture the complex interplay of factors influencing longevity. Artificial Intelligence (AI), particularly machine learning (ML) techniques, has emerged as a powerful tool to address this challenge. This paper delves into the application of AI for mortality risk prediction in life insurance, exploring various techniques, model development processes, validation strategies, and real-world implementations for improved underwriting decisions. The paper commences with an overview of the life insurance underwriting process, highlighting the significance of accurate mortality risk assessment. We then discuss the limitations of traditional methods, emphasizing the inability to capture emerging risk factors and potential biases in human judgment. Subsequently, the paper delves into the theoretical underpinnings of AI and ML, particularly supervised learning algorithms commonly employed for mortality risk prediction. Techniques such as logistic regression, random forests, and gradient boosting are explored, along with their strengths and weaknesses in this specific context. A crucial aspect of this paper is the detailed exploration of model development and validation processes. We discuss data acquisition strategies, emphasizing the importance of data quality, diversity, and ethical considerations. Feature engineering techniques for transforming raw data into meaningful predictors for AI models are elaborated upon. The paper sheds light on model training methodologies, including cross-validation and hyperparameter tuning, to optimize model performance and prevent overfitting. Validation of AI models for life insurance applications is paramount. We discuss various validation metrics relevant to mortality risk prediction, such as Area Under the Curve (AUC) and Brier Score. Techniques for assessing model calibration and fairness are also explored, ensuring reliable and unbiased predictions. Addressing the potential for bias in AI models due to inherent biases in training data or algorithmic design is crucial. The paper examines mitigation strategies such as fairness-aware data pre-processing and model interpretability techniques like SHAP (SHapley Additive exPlanations) values. Following a thorough discussion of model development and validation, the paper transitions to exploring real-world applications of AI for mortality risk prediction in life insurance. We examine how AI can streamline underwriting processes by automating tasks and facilitating faster decision-making. The potential for personalized premiums based on individual risk profiles is explored, enabling a more just and competitive insurance market. Additionally, the paper discusses the role of AI in risk-based product development, allowing insurers to cater to specific customer segments with tailored insurance solutions. The concluding section of the paper emphasizes the transformative potential of AI for the life insurance industry. While acknowledging the ethical considerations and regulatory hurdles surrounding the use of AI in insurance, the paper underscores the potential benefits of improved risk assessment, streamlined processes, and ultimately, a more efficient and inclusive insurance market. We propose future research directions, highlighting the need for continuous model development, robust validation frameworks, and ongoing efforts to ensure fairness and explainability in AI-powered underwriting.